Enantioselective Synthesis of Cassane‐Type Furanoditerpenoids: Total Synthesis of Sucutiniranes C and D. Issue 30 (20th July 2020) - Pitsinos, Emmanuel N.; Mavridis, Ioannis; Tzouma, Eirini; Vidali, Veroniki P.
Abstract : The first enantioselective total synthesis of cassane‐type furanoditerpenoids featuring an aromatic C ring and a substituted B ring is presented. The strategy employed relied on diastereoselective Diels–Alder (DA) reaction of an enantiomerically pure 1, 3, 3‐trisubstituted‐2‐vinyl‐cyclohexene (sterically demanding diene). It was secured in > 99 % ee through elaboration of enzymatically resolved 3‐ethoxy‐6‐(hydroxymethyl)‐6‐methyl‐cyclohex‐2‐en‐1‐one. Employing hexafluoro‐2‐propanol (HFIP) as the solvent, its DA cycloaddition onto benzo[ b ]furan‐4, 7‐dione proceeded with exquisite endo ‐selectivity under ambient temperature and pressure. Subsequent diastereo‐ and regio‐selective methyl Grignard addition provided a pivotal intermediate featuring the complete vouacapane framework. Its versatility and intriguing reactivity were demonstrated by conversion to sucutiniranes C and D. Abstract : Intriguing reactivities were encountered en route to the first total synthesis of aromatic C ring vouacapanes featuring a substituted B ring (III and IV ) through exploitation of the pivotal intermediate II . A new modification of the Caglioti reaction had to be developed to allow efficient reductive deoxygenation at low temperature.